JOY AS A PERCEIVED CHOICE IN ANTHROPOLOGY OF CHESTERTON - Moskvin, Y. V. (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2017)
The article concerns with philosophical views of English writer, journalist, Christian apologist Gilbert Keith Chesterton. It deals with critics of modernism and postmodernism projects. Anthropology of Chesterton connected with theology and tradition, but it has unique character, because it is still relevant. Chesterton writes about ideas that drives people and shows that philosophy has of significant importance in life. The conclusion is made that Chesterton’s philosophy shows the joy as ontological category.